Inovasi Dalam Pembelajaran Bahasa: Teknologi dan Media Untuk Anak Usia Dini - Febriana, Ika; Treasia, Eva; Purba, Glory Verentina Sari; Parinduri, Aulia Rohmah; Sirait, Riris; Buulolo, Sefrin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Children are increasingly involved with various digital technologies in everyday life and are becoming their users. This research aims to understand the application of communication technology in language learning for early childhood. This study used descriptive qualitative method. In the learning process, communication technology is used ax a tool to support children’s language learning. Activities carried out by teachers involve the use of pictures, word videos, practice videos, as well as words and sounds. Based on observations, several teachers have implemented and practiced information and communication technology devices to make it easier for children to find information, expecially in the area of language. Based on the results of this research, it can be concluded that information and communication technology is applied effectively in language learning at the early age level.